Report on research, innovation and technological performance in Germany 2024 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2024)
Foreword: The Commission of Experts for Research and Innovation presents its 2024 Annual Report to the German Federal Government in particularly challenging political times. Issues such as the wars in Ukraine, Israel and the Gaza Strip, the energy crisis and the economic downturn are dominating the political discourse. They all demand the attention of the Federal Government and require its immediate action. But at the same time, and this is the particular challenge for the politics of our time, the focus on these acute problems must not lead to neglecting the necessary transformation of the economy and society towards sustainability based on technological and social innovation. Postponing transformation efforts would not only have dangerous ecological consequences but would also jeopardize the basis of our medium- and long-term prosperity and social stability. The 2024 Annual Report of the Commission of Experts for Research and Innovation should be read against the background of this tension between multiple current crises on the one hand and long-term transformation requirements on the other. In addition to statements on how transformation-oriented research and innovation policy should be designed in this situation, the Annual Report contains, as in previous years, commentaries on current research and innovation policy as well as analyses of key topics and problem areas in the German research and innovation system. The much-discussed topic of artificial intelligence certainly features prominently here. However, the Annual Report is also dedicated to less widely discussed topics that should be given more attention in the future. These include agriculture and its transformation potential, the international mobility of researchers and the associated question of Germany's attractiveness as a location for science and innovation, as well as social innovations and their role in transformative change.
Keywords: 330